Effects of glucosamine on the tibial epiphyseal disk of ovariectomized rats: morphologic and morphometric analysis Efeitos da terapia de reposição hormonal estroprogestativa sobre o sistema de coagulação e de fibrinólise em mulheres na pós-menopausa - Carla C Maganhin (Clinics, 2007)
OBJECTIVE: The aim of this study was to analyze the effect of glucosamine sulfate on the tibial epiphyseal disk of the ovariectomized rats. METHODS: After ovariectomy (OVx), 28 female rats were randomly divided into 4 experimental groups with 7 animals each, treated as follows: OVx 21 - vehicle (NaCl 0.9%) 0.5 mL/day) for 21 days; OVx GS21 - 230 mg/kg/day glucosamine sulphate for 21 days; OVx 45 - treated with NaCl 0.9% as above for 45 days; and OVx - GS45230 mg/kg/day glucosamine sulphate for 45 days. Seven intact animals in the proestrous phase were used as controls (CG). Upon treatment completion, the animals were sacrificed and the left knee joint was dissected and prepared for histological analysis. RESULTS: The percentage of remaining cartilage in new bone of the CG; that found in THE OVx GS45 group was significantly less than that of the OVx 21, OVx GS21, and OVx 45 groups. The percentage of trabecular bone in proestrous animals was the highest. The OVx GS45 group showed higher values compared with the other ovariectomized groups. These results were paralleled by the findings regarding the cells of the proliferative zone, since the CG had the highest values, and the values of the OVx GS45 group were greater than those of the OVx 21, OVx GS21, and OVx 45 groups. CONCLUSION: Our studies suggested that glucosamine may stimulate tibial cartilage and bone growth after ovariectomy in rats. OBJETIVO: O alvo deste estudo foi analisar o efeito do sulfato de glicosamina no disco epifisário da tíbia em ratas ooforectomizadas. MÉTODOS: Após a ooforectomia (OVx), 28 ratas foram aleatoriamente divididas em 4 grupos experimentais de 7 animais cada, tratados da seguinte maneira: OVx 21 - veículo (0,5ml de NaCl 0.9% ip uma vez ao dia) por 21 dias; OVx GS21 230 - mg/kg peso corporal por dia de sulfato de glicosamina, 21 dias; OVx 45 - tratados com NaCl 0.9% igual ao grupo OVx 21, por 45 dias; e OVx GS45 - 230 mg/kg peso corporal por dia com sulfato de glicosamina, 45 dias. Sete animais intactos, na fase de proestro, foram usados como controle (CG). Ao completar o tratamento, os animais foram sacrificados e a articulação do joelho esquerdo foi dissecada e preparada para análise histológica. RESULTADOS: A porcentagem de cartilagem remanescente no novo osso do CG foi a menor. Os achados no grupo OVx GS45 foi significantemente menor do que no grupo OVx 21, OVx GS21 e OVx 45. A porcentagem de osso trabecular nos animais em pró-estro foi a maior. O grupo OVx GS45 mostrou valores maiores em relação aos outros grupos ooforectomizados. Esses resultados foram correspondentes aos achados em relação às células da zona proliferativa, desde que o CG teve os maiores valores e os valores do grupo OVx GS45 foram superiores aos dos grupos OVx 21, OVx GS21 e OVx 45. CONCLUSÃO: Nossos estudos sugerem que a glicosamina pode estimular o crescimento da cartilagem e do osso tibial após a ooforectomia em ratas.